JUUL in School: Teacher and Administrator Awareness and Policies of E-Cigarettes and JUUL in U.S. Middle and High Schools. Issue 1 (January 2020) - Schillo, Barbara A.; Cuccia, Alison F.; Patel, Minal; Simard, Bethany; Donovan, Emily M.; Hair, Elizabeth C.; Vallone, Donna
Electronic cigarette (e-cigarette) use, including JUUL, has risen to epidemic levels among high school and middle school students in the United States. Schools serve as a key environment for prevention and intervention efforts to address e-cigarette use, yet little is known about the awareness of and response to e-cigarettes in schools. This national survey of middle and high school teachers and administrators ( n = 1, 420) measured JUUL awareness, e-cigarette policies, and barriers to enforcement in schools. While two thirds of respondents had heard of a product called JUUL (67.6%), less than half accurately identified a photo of a JUUL as a vaping device/e-cigarette (47.3%). Awareness of JUUL (80.9%) was higher among high school teachers (83.3%) than among middle school teachers (78.3%). A large majority of respondents reported that their school had an e-cigarette policy (82.9%), but less than half of the sample worked in a school with a policy that specifically included JUUL (43.4%). Those working in a school with an e-cigarette policy in place noted that e-cigarettes' discreet appearance (65.6%) and difficulties in identifying origin of vapor or scent (46.1%) made the policy difficult to enforce. Efforts to increase middle and high school staff awareness of the ever-evolving e-cigarette market are essential to help prevent youth use. Adoption and enforcement of policies will be critical to ensure that schools remain tobacco-free spaces.